Experimental investigation of the effect of inlet particle properties on the capture efficiency in an exhaust particulate filter. (November 2017) - Viswanathan, Sandeep; Rothamer, David; Zelenyuk, Alla; Stewart, Mark; Bell, David
Abstract: The impact of inlet particle properties on the filtration performance of clean and particulate matter (PM) laden cordierite filter samples was evaluated using PM generated by a spark-ignition direct-injection (SIDI) engine fuelled with tier II EEE certification gasoline. Prior to the filtration experiments, an advanced aerosol characterization system that comprised of a scanning mobility particle spectrometer (SMPS), centrifugal particle mass analyzer (CPMA), a differential mobility analyzer (DMA), and a single particle mass spectrometer (SPLAT II) was used to obtain a wide range of information on the SIDI PM emissions including particle size distribution (PSD), composition, mass, and dynamic shape factors (DSFs) in the transition ( χ t ) and free-molecular ( χ v ) flow regimes. During the filtration experiments, real-time measurements of PSDs upstream and downstream of the filter sample were used to estimate the filtration performance and the total trapped mass within the filter using an integrated particle size distribution method. The filter loading process was paused multiple times to evaluate the filtration performance in the partially loaded state. The change in vacuum aerodynamic diameter ( d va ) distribution of mass-selected particles was examined for flow through the filter to identify whether preferential capture of particles of certain shapes occurred in the filter. The filter was also probed using different inlet PSDs. Pausing the filter loading process and subsequently performing the filter probing experiments did not impact the overall evolution of filtration performance. Within the present distribution of particle sizes, filter efficiency was independent of particle shape potentially due to the diffusion-dominant filtration process. Particle mobility diameter and trapped mass within the filter appeared to be the dominant parameters that impacted filter performance. Highlights: Effects of inlet particle properties on filtration performance were evaluated. Diffusion was dominated capture mechanism for the size range explore. Average dynamic shape factors were characterized in multiple flow regimes. Size-resolved FE was relatively insensitive to mobility diameter beyond the MPPS. Within observed distribution of shapes, filter efficiency was independent of shape.